An updated description of the osteology of the pancake tortoise Malacochersus tornieri (Testudines: Testudinidae) with special focus on intraspecific variation. (25th January 2017) - Mautner, Anna‐Katharina; Latimer, Ashley E.; Fritz, Uwe; Scheyer, Torsten M.
ABSTRACT: Exceptional variability in the shell of the pancake tortoise Malacochersus tornieri, both in the keratinous surficial scutes and the underlying bones, in addition to its remarkably fenestrated bony shell are unique among tortoises. Based on 14 individuals of different sizes and ages, the observed variation in M. tornieri was described in detail, with additional notes on the typically testudinid skull, inner ear and brain endocast using microCT‐scan data, as well as the limbs. Similar degrees of variation have not yet been described in any other extant turtle species and therefore seem notable in M. tornieri, and might be related to the species' unique lifestyle. Within the carapace, the peripherals and suprapygals are most variable in number. Furthermore, different combinations of peripherals are participating in the central plastral fontanelle and in some individuals additional bones take part in the formation of the plastron. J. Morphol. 278:321–333, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Interpretative drawings of the carapaces of three individuals of the pancake tortoise, Malacochersus tornieri, indicating the high levels of variation in bone morphology, bone element numbers, and scute pattern. Solid lines: bones, stippled lines: scute imprints on the bones, gray: fontanelle.